Comparison of a morning polypill, evening polypill and individual pills on LDL-cholesterol, ambulatory blood pressure and adherence in high-risk patients; a randomized crossover trial. (15th February 2015) - Lafeber, M.; Grobbee, D.E.; Schrover, I.M.; Thom, S.; Webster, R.; Rodgers, A.; Visseren, F.L.J.; Bots, M.L.; Spiering, W.
Abstract: Aims: Cardiovascular polypills are a novel strategy in the prevention of cardiovascular disease. Based on considerations about the effectiveness, the individual pills of a polypill are taken at different times of the day. This study aimed therefore to compare the use of a polypill in the morning, in the evening or the individual components taken at their usual times on cardiovascular risk factors and patient acceptability. Methods: The study was a randomized three-period crossover trial. Seventy-eight patients with established cardiovascular disease were randomly allocated to the use of polypill (aspirin 75 mg, simvastatin 40 mg, lisinopril 10 mg and hydrochlorothiazide 12.5 mg) in the morning, in the evening or use of the individual agents taken at different time points (Trial:NCT01506505 ). Results: Using the polypill in the evening resulted in a 0.2 mmol/L (95%-confidence interval (CI): 0.1 to 0.3) lower fasting LDL-cholesterol compared to the use in the morning, and not statistically significantly different mean 24-hour systolic BP (mean difference: 0.7 mm Hg; 95%-CI; − 2.1 to 3.4). Compared to the use of the individual agents, the mean LDL-cholesterol was 0.2 mmol/L (95%-CI: 0.1 to 0.3) higher when using the polypill in the morning, but not statistically significantly different when used in the evening (mean difference: − 0.1 mmol/L; 95%-CI: − 0.1 to 0.0). Furthermore, there were no differences in mean 24-hour systolic BP with morning use (mean difference: 0.4 mm Hg; 95%-CI; − 1.5 to 2.3) or evening use (mean difference: 1.0 mm Hg; 95%-CI; − 0.8 to 2.8) of the polypill compared to the individual agents. The adherence was 5.2% (95%-CI: 1.4 to 9.1) higher with morning use of the polypill and 5.0% (95%-CI: 1.5 to 8.5) higher with evening use compared to the individual agents. Treatment with the polypill was preferred by 92% of the participants. Conclusion: The use of a polypill in the evening was more effective in lowering LDL-cholesterol, and resulted in not statistically significantly different ambulatory BP levels compared to the use of a polypill in the morning. Therapy with a polypill was associated with an increased adherence. The polypill is highly preferred by patients, demonstrating a potential role for the polypill in the prevention of cardiovascular disease.